2021
DOI: 10.1097/ccm.0000000000005169
|View full text |Cite
|
Sign up to set email alerts
|

Descriptors of Sepsis Using the Sepsis-3 Criteria: A Cohort Study in Critical Care Units Within the U.K. National Institute for Health Research Critical Care Health Informatics Collaborative*

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 33 publications
4
40
0
Order By: Relevance
“…Many advocate the use of clinical data to define the epidemiology of sepsis. 18 , 22 , 23 , 24 In a study of data from 7 health systems, Rhee et al 24 identified sepsis hospitalizations using clinical data such as blood cultures, antibiotic and vasopressor administration, mechanical ventilation, and laboratory test measures. The incidence of sepsis in the Rhee et al 24 study was 60 per 1000 hospitalizations; although lower than the Angus estimate and higher than the explicit sepsis estimate, this figure is very similar to the Martin et al 6 and SEP‐1 estimates observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Many advocate the use of clinical data to define the epidemiology of sepsis. 18 , 22 , 23 , 24 In a study of data from 7 health systems, Rhee et al 24 identified sepsis hospitalizations using clinical data such as blood cultures, antibiotic and vasopressor administration, mechanical ventilation, and laboratory test measures. The incidence of sepsis in the Rhee et al 24 study was 60 per 1000 hospitalizations; although lower than the Angus estimate and higher than the explicit sepsis estimate, this figure is very similar to the Martin et al 6 and SEP‐1 estimates observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, at least three missing SOFA components resulted in discarding any identification of sepsis or not for that admission/day. Following [3], we define infection by an increase in the maximum rank of any antibiotics administered (or the number of antibiotics of maximum rank), according to the classification proposed by [14], where at least one antibiotic was given intravenously. This operationalisation of Sepsis-3 with a suspected infection identified only by antibiotic escalation is reliant on clinical judgement rather than a confirmed infection, which is a limitation of this approach.…”
Section: Implementation Sepsis-3 In Amsterdam Umc Databasementioning
confidence: 99%
“…The study by Shah et al (13) provides further evidence that Sepsis-3 criteria can be successfully operationalized using EHR data, including in multicenter settings. The promise of this approach is clear: with the growing national and international adoption of EHR systems, consistent electronic application of Sepsis-3 criteria could generate standardized and risk-adjusted estimates of sepsis incidence, outcomes, and trends.…”
mentioning
confidence: 97%
“…Underscoring this challenge, a recent medical record review-based study demonstrated wide variability in the sensitivity and specificity of commonly used EHR-based definitions of infection (14). Notably, the study by Shah et al (13) used a novel definition based on new antibiotics or antibiotic escalation alone, without the concurrent requirement for obtaining blood or clinical cultures that most prior studies have used. This is an approach optimized for sensitivity but may come at the cost of specificity given the proclivity of many providers to err on the side of treating empirically when the diagnosis of infection is possible but unconfirmed, particularly in critically ill patients (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation